Strategi Manajemen Pengelolaan Peluang Bisnis F&B Sebagai Upaya Mengatasi Permasalahan Ekonomi Keluarga dengan Pemanfaatan Teknologi Digital - Jandrianto Patandianan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of completing this journal writing is to provide a new perspective on the development of F&B (food and beverage) businesses in the era of technological development. With the hope that it will help families in managing and developing businesses owned by a family with the use of digital technology, within the framework of the logo perspective of family counseling assistance which is a theory that can help the implementation of this F&B business, with implications for being able to overcome economic problems in a family. The research method used is a descriptive qualitative method, namely by presenting data related to the economic situation of a family that has an F&B business, then providing a descriptive form of response to the family's economic problems, which will help the family to develop a food and beverage business by utilizing digital technology. , to overcome family economic problems. An approach using family counseling logo theory will provide the essence of improving quality in running an F&B business in the digital era.